Clinical outcomes and functional recovery following hemiarthroplasty for unstable hip / intertrochanteric fractures in elderly patient: A review of 40 cases at CBMCB Hospital (2020-2023) (Community Based Medical Journal, 2025)
Unstable intertrochanteric fractures in the elderly population often lead to significant morbidity and disability, necessitating surgical intervention. Hemiarthroplasty is considered an effective surgical treatment for managing these fractures, especially in frail elderly patients. This study aims to evaluate the clinical and functional outcomes of hemiarthroplasty for unstable intertrochanteric fractures in elderly patients, with a retrospective analysis of 40 cases treated at CBMCB Hospital. We analyzed surgical outcomes, recovery rates, complications, and functional assessments. Most patients (85%) were mobilized within 48 hours postoperatively. The mean hospital stay was 6.5 days. At the end of 12 months, 70% of patients had good to excellent outcomes based on the Harris Hip Score. The results suggest that hemiarthroplasty provides satisfactory functional recovery, but complications such as infections and dislocations remain important considerations. This study highlights the need for individualized management in the elderly and underscores the importance of early postoperative rehabilitation.  CBMJ 2025 July: vol. 14 no. 02 P:158-167